KONSTRUKSI KEILMUAN SAINS DAN MATEMATIKA DALAM PERSPEKTIF ISLAM SERTA IMPLEMENTASINYA PADA LEMBAGA PENDIDIKAN ISLAM - Zaenuri, Ahmad; Irfan, Ahmad (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
The relationship between science and religion in the construction of Islamic knowledge tends to be dynamic. On one hand, some scholars argue that science and religion are two distinct entities, each with its own domain of study. On the other hand, others believe that there is a dialectical (integrated) relationship between science and religion, wherein they can complement each other's deficiencies. Science without religion may lose its values and ethics, while religion without science may lack the scientific dimension as a fundamental part of established knowledge construction. The aim of this research is to analyze in-depth the relationship between science, religion, and mathematics from an Islamic perspective. The analysis is conducted through library research, utilizing various reputable literature such as books and scientific journals. The findings of this research indicate that the relationship between science and religion (Islam) can take at least four forms: conflict, independence, dialogue, and integration. This conclusion is drawn from the perspectives of several scholars, including Ian G. Barbour, Fazlur Rahman, Ismail Raji Al-Faruqi, Muhammad Nauquib Al-Attas, Mulyadhi Kartanegara, and Muhammad Amin Abdullah. The conflict between science and religion is not exclusive to Islam but is also observed in Christianity when philosophical views are deemed contradictory to church dogmas. The debate between science, philosophy, and religion in Islam began with Imam Al-Ghazali's critique of philosophical constructs in his work "Tahafut al-Falasifah" (The Incoherence of the Philosophers), which was responded to by Ibn Rushd with his work "Tahafut al-Tahafut" (The Incoherence of the Incoherence). To bridge the scholarly dichotomy, Muslim scholars propose the concept of interdisciplinary integration between religious sciences (al-ulÅ«m al-dÄ«niyah) and general sciences or philosophy (al-ulÅ«m al-â€˜alamiyah / al-falÄsifah).